A Closer Look at the Costs of Serving Children "Living on the Edges" of State School Finance Policy: At-Risk, Limited English Proficient, and Gifted Children - Bruce D. Baker (Educational Considerations, 2004)
Considerable attention has been given over the years to understanding the costs of serving students with disabilities and the design of state funding systems for ensuring that students’ special needs can be met by local districts.